'Tu ga na inima ka luvu na waqa' : (The bail to get water out of the boat is in the boat yet the boat sinks) : the cultural constructs of health and wellbeing amongst Marama iTaukei in a Fijian village in Lau and in a transnational Fijian community in Whanganui, Aotearoa : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Social Policy at Massey University, Palmerston North, Aotearoa - Meo-Sewabu, Litea Diloki (Massey University, 2015)
The study identified that there are a number of criteria that have to be met in order for 𝘔𝘢𝘳𝘢𝘮𝘢 𝘪𝘛𝘢𝘶𝘬𝘦𝘪 or Indigenous Fijian woman to be perceived as healthy. Findings suggest that current health frameworks need to take into account the determinants of health that are informed by cultural constructs that emerged as key findings in this study including: 𝘋𝘢𝘶 𝘷𝘦𝘪𝘲𝘢𝘳𝘢𝘷𝘪 or being of service, 𝘛𝘢𝘶𝘤𝘰𝘬𝘰 𝘯𝘪 𝘲𝘢𝘳𝘢𝘷𝘪 𝘪𝘵𝘢𝘷𝘪 or completion and completeness of tasks, 𝘕𝘢 𝘷𝘦𝘪𝘸𝘦𝘬𝘢𝘯𝘪 or maintaining harmony in relationships and 𝘒𝘦𝘯𝘢 𝘐 𝘳𝘢𝘪𝘳𝘢𝘪 outward reflection or physical appearance and 𝘉𝘶𝘭𝘢 𝘷𝘢𝘬𝘢𝘺𝘢𝘭𝘰 or Spirituality. Exploring the intricate and delicate weaving of Fijian epistemologies and Western philosophies as illustrated through the 𝘛𝘢𝘯𝘰𝘢 𝘏𝘦𝘢𝘭𝘵𝘩 𝘉𝘦𝘭𝘪𝘦𝘧 𝘍𝘳𝘢𝘮𝘦𝘸𝘰𝘳𝘬 emerging from the findings in this thesis, may ideally be the future to improving health and wellbeing for, 𝘔𝘢𝘳𝘢𝘮𝘢 𝘪𝘛𝘢𝘶𝘬𝘦𝘪. The 𝘛𝘢𝘯𝘰𝘢 𝘏𝘦𝘢𝘭𝘵𝘩 𝘉𝘦𝘭𝘪𝘦𝘧 𝘍𝘳𝘢𝘮𝘦𝘸𝘰𝘳𝘬 has been developed to assist health and community workers to assess the determinants of health and wellbeing amongst Fijian women. This was a qualitative study with a total of 23 participants conducted in two geographical locations, one in Fiji and one in Aotearoa. The study was not a comparative study however; the study in Fiji enabled an exploration of how perceptions and experiences of health and wellbeing have evolved as Fijian women have migrated to Aotearoa. Ethnography was used as the overarching methodology as well as the 𝘝𝘢𝘯𝘶𝘢 methodology. Methods used included 𝘵𝘢𝘭𝘢𝘯𝘰𝘢, participant observation and photovoice. In terms of methodology, a 𝘛𝘢𝘭𝘪 𝘮𝘢𝘨𝘪𝘮𝘢𝘨𝘪 𝘍𝘳𝘢𝘮𝘦𝘸𝘰𝘳𝘬 pulled together the strands of what constitutes this thesis. This includes the process of ‘𝘤𝘶𝘭𝘵𝘶𝘳𝘢𝘭 𝘥𝘪𝘴𝘤𝘦𝘳𝘯𝘮𝘦𝘯𝘵’ emerging from the ethics process encountered in this research. The concept of ‘𝘤𝘶𝘭𝘵𝘶𝘳𝘢𝘭𝘭𝘺 𝘦𝘮𝘣𝘦𝘥𝘥𝘦𝘥 𝘢𝘨𝘦𝘯𝘤𝘺’ is also presented in this thesis arguing that there needs to be an agency-oriented approach to women’s agenda. Culturally embedded agency calls for social policy that incorporates full participation of women in society, inclusive of indigeneity goals, cultural wellbeing and fairness. Implications of this study and recommendations are based on ensuring that health and wellbeing is achieved for the 𝘔𝘢𝘳𝘢𝘮𝘢 𝘪𝘛𝘢𝘶𝘬𝘦𝘪.
Keywords: Women; Fijians; Health and hygiene; Lau Province; Fiji; Whangarei; Aotearoa; New Zealand; Marama iTaukei